Relationship between fecal egg count, parasite load, and histopathological findings in the pancreas of cattle naturally infected with Eurytrema coelomaticum - Pantiu, Andrea Julia; Haberle, Tomás Joaquín; Avellaneda Cáceres, Agustín; Olmos, Leandro Hipólito; Ruiz, Álvaro Francisco; Signorini Porchiett, Marcelo Lisandro; Micheloud, Juan Francisco (Elsevier, 2025)
Eurytrematosis, a disease caused by Eurytrema spp., primarily affects the pancreas of mammals, including cattle. Although common in Africa, Asia and South America, Eurytrema coelomaticum has recently been detected in Argentina. The present study aimed to evaluate the relationship between parasite load, fecal egg counts (EPG) using two diagnostic techniques (BST and OST), and histopathological lesions in cattle naturally infected with Eurytrema. A total of 120 cattle from an endemic area were selected for the study, with both pancreatic and fecal samples collected for parasitological and histopathological analysis. Histopathological lesions were classified into three grades based on the severity of pancreatic damage. The results demonstrated a significant difference between the parasitic load and the severity of pancreatic lesions (P= 0.001). Both diagnostic techniques demonstrated a significant difference between parasite presence and lesion severity; however, the OST showed higher sensitivity (88 %) and fewer false negatives (12 %) compared to the BST, which exhibited 65 % sensitivity and 35 % false negatives. Histopathological findings revealed more severe lesions, such as fibrosis and interstitial inflammation, in animals with higher parasite loads. These results emphasize the importance of combining reliable diagnostic techniques like OST with histopathological analysis to improve the understanding and management of eurytrematosis in cattle. The findings provide valuable insights into the disease's impact and suggest strategies for controlling its effects on livestock health and productivity.